Effect of oat-based edible protective coating on quality and shelf life of broccoli heads stored at refrigerated temperature - Pandith, Junaid Ahmad; Ahmad , Saghir (Journal of Postharvest Technology, 2023)
The effectiveness of oat starch (OS) and cinnamon essential oil (CEO) based edible coatings on fresh-cut broccoli's quality aspects and shelf  life for 21 days at ± 5 °C were studied. Oat-based natural coatings were determined to preserve broccoli quality features and improve its shelf life effectively. Compared to coated samples, untreated broccoli showed a much higher percentage weight loss. The greenness (-a*) values  during the course of storage showed that treated samples had less yellowing and greater green color retention than untreated samples. Oat  starch-coated samples consistently showed lower ascorbic acid and chlorophyll degradation rates than untreated samples. The total plate count  and yeast and mold load increased in all samples throughout the storage; untreated samples experienced a greater increase in microbial load.  However, the treated ones were effective in maintaining low microbial loads, particularly the treatments with 2% OS + 0.5% CEO in maintaining  lower microbial populations. The broccoli heads treated with different coating compositions received a higher score on sensory evaluation than  the uncoated sample; however, coatings with CEO received a little lower score on sensory character aroma.
Keywords: Edible coating; fresh-cut-vegetables; minimal processing; oat-based-coating; shelf-life